2000
DOI: 10.1073/pnas.97.13.7573
|View full text |Cite
|
Sign up to set email alerts
|

Immunogold evidence that neuronal gap junctions in adult rat brain and spinal cord contain connexin-36 but not connexin-32 or connexin-43

Abstract: Physiological and ultrastructural evidence indicates that gap junctions link many classes of neurons in mammalian central nervous system (CNS), allowing direct electrical and metabolic communication. Among at least six gap junction-forming connexin proteins in adult rat brain, connexin-(Cx) 32, Cx36, and Cx43 have been reported to occur in neurons. However, no connexin has been documented at ultrastructurally defined neuronal gap junctions. To address this question directly, freeze-fracture replica immunogold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
239
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(259 citation statements)
references
References 46 publications
17
239
1
2
Order By: Relevance
“…In light of ultrastructural evidence indicating extensive gap junctions between astrocytes and between astrocytes and oligodendrocytes, and the absence of intercellular gap junction formation between oligodendrocytes (Mugnaini, 1986;Rash et al, , 2000, it is clear that the astrocytic Cxs participate in the formation of A/A junctions, and contribute these Cxs to the astrocyte side of A/O gap junctions. Less clear and requiring detailed ultrastructural investigation, however, is the extent to which oligodendrocyte cell populations express each of Cx29, Cx32 and Cx47; the oligodendrocyte cellular compartments in which these Cxs are concentrated; and the nature of the gap junctional channels in which they engage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of ultrastructural evidence indicating extensive gap junctions between astrocytes and between astrocytes and oligodendrocytes, and the absence of intercellular gap junction formation between oligodendrocytes (Mugnaini, 1986;Rash et al, , 2000, it is clear that the astrocytic Cxs participate in the formation of A/A junctions, and contribute these Cxs to the astrocyte side of A/O gap junctions. Less clear and requiring detailed ultrastructural investigation, however, is the extent to which oligodendrocyte cell populations express each of Cx29, Cx32 and Cx47; the oligodendrocyte cellular compartments in which these Cxs are concentrated; and the nature of the gap junctional channels in which they engage.…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, astrocytes are extensively coupled by gap junctions (astrocyte-toastrocyte gap junctions [A/A junctions]) that, based on ultrastructural observations, were reported to contain Cx26, Cx30 and Cx43 (Yamamoto et al, 1990a,b;Nagy et al, 1999Nagy et al, , 2001. Also present are astrocyte-to-oligodendrocyte gap junctions (A/O junctions) that contain the former three Cxs on the astrocyte side, and Cx32 on the oligodendrocyte side Rash et al, 2000Rash et al, , 2001Nagy and Rash, 2000;Nagy et al, 2003a). Recently, it was reported that oligodendrocytes also express Cx47 (Odermatt et al, 2003) as well as Cx29, with conflicting results indicating either that mutually exclusive populations of these cells contain Cx29 and Cx32 (Altevogt et al, 2002), or that many of these cells contain both of these Cxs (Nagy et al, 2003a,b).…”
mentioning
confidence: 99%
“…Sternberger Monoclonals * For FRIL, all antibodies were used at 10 μg/ml. ** Previously characterized in Rash et al (2000) aa, amino acids…”
Section: Tbstrmentioning
confidence: 99%
“…749.11, 2002) for immunocytochemical precedent, Long and coworkers (Long et al, 2005) proposed Cx36 as the primary or sole connexin in neuronal gap junctions in SCN, and suggested that Cx36 deletion disrupted circadian rhythms. Among the 21 connexins known to be present in mammals (Condorelli et al, 1998;Söhl and Willecke, 2003;Willecke et al, 2002), both Cx36 and Cx45 have been demonstrated in ultrastructurally-defined neuronal gap junctions (Rash et al, 2000(Rash et al, , 2001Fukuda et al, 2006;Kamasawa et al, 2006), and there is immunocytochemical evidence for neuronal expression of Cx50 and Cx57 in retina (Massey et al, 2003;Hombach et al, 2004;O'Brien et al, 2006). In view of controversies surrounding the existence and connexin composition of neuronal gap junctions in SCN, we used confocal immunofluorescence microscopy and freeze-fracture replica immunogold labeling (FRIL) to document gap junctions in SCN neurons and to identify the constituent connexins in neurons vs. glia, and whole-cell recordings from hypothalamic slices to re-assess tracer and electrotonic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…18 A expressão da conexina-36 é restrita aos neurônios, enquanto a conexina-32 e a conexina-43 são encontradas em oligodendrócitos e astrócitos, respectivamente. 18,24 Recentemente, o papel das JC na geração de crise tem sido estudado com mais detalhes em modelos de epilepsia in vivo, in vitro, em simulações computacionais e em humanos. Estudos eletrofisiológicos têm implicado as JC na geração de oscilações muito rápidas (OMR) precedendo as crises.…”
Section: Introductionunclassified